Expedited extraction of xylan from lignocellulosic biomass by power ultrasound - Yang, Wade; Aljapur, Vishnu K.; Krishnamurthy, Kathiravan; Feng, Hao; Yang, Ruijin; Rababah, Taha M. (International Journal of Agricultural and Biological Engineering, 2010)
Some lignocellulosic biomass like corncob contains a large amount of xylan, a valuable material for applications in food, chemical and pharmaceutical industries. Conventional extraction of xylan is a time consuming process, requiring 12 to 24 hours to complete. In this study, the efficacy of power ultrasound for reducing the extraction time and increasing the xylan yield was investigated. Two acoustic energy densities (0.18 W/mL and 0.45 W/mL) of the power ultrasound were applied to corncob for 10, 20, 30, and 60 min. The treated samples were steamed at 110, 118 and 121<span style="font-family: